Organizational Culture and Job Satisfaction towards Organizational Citizenship Behavior (OCB): The Role of Loyalty as Mediation (International Journal of Scientific Research and Management (IJSRM), 2024)
The present investigative research endeavors to scrutinize the correlational dynamics between Organizational Culture and Job Satisfaction in relation to Organizational Citizenship Behavior (OCB), with Loyalty functioning as an intermediary mechanism. The research population encompasses all permanent personnel, comprising a total of 154 individuals; the investigative sampling methodology employed a comprehensive census approach, systematically including all permanent employees across Owabong Waterpark, Sanggaluri Park, and Golaga within Purbalingga Regency. The Purpose of this study was to determine the extent of influence of Organizational Culture and Job Satisfaction on Organizational Citizenship Behavior with Loyalty as a Mediator. Empirical data were procured through structured questionnaire instruments, with subsequent analytical processing conducted utilizing SmartPLS 4.1 statistical software. The comprehensive analytical findings revealed multifaceted significant relational patterns:Organizational Culture demonstrated a statistically significant positive correlation with OCB,Job Satisfaction exhibited a statistically significant positive influence on OCB,Organizational Culture manifested a statistically significant positive impact on Loyalty,Job Satisfaction presented a statistically significant positive relationship with Loyalty,Loyalty demonstrated a statistically significant positive effect on OCB,Organizational Culture demonstrated a statistically significant positive influence on OCB through Loyalty as an intermediary variable,Job Satisfaction indicated a statistically significant positive impact on OCB via Loyalty as a mediating mechanism.The research substantiates that personnel experiencing elevated levels of job satisfaction and perceiving a robust, supportive organizational culture are substantially more predisposed to augment organizational loyalty, which subsequently catalyzes enhanced Organizational Citizenship Behavior, ultimately generating comprehensive organizational benefits.